ENCYCLOPEDIA Britannica 2009 book of the year / editor, Karen Jacobs Sparks...[et al] ; ilustrrasi, Thomas J. Sponos. - Sparks, Karen Jacobs; Spanos, Thomas J. (Britannica, 2009)
880 hlm. : ilus. ; 27 cm (2 eks.)